2016
DOI: 10.1007/s10532-016-9756-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferrous chloride on biogas production and enzymatic activities during anaerobic fermentation of cow dung and Phragmites straw

Abstract: The effect of ferrous (added as FeCl2) on the anaerobic co-digestion of Phragmites straw and cow dung was studied by investigating the biogas properties, pH values, organic matter degradation (COD) and enzyme activities (cellulase, protease and dehydrogenase) at different stages of mesophilic fermentation. The results showed that Fe(2+) addition increased the cumulative biogas yields by 18.1 % by extending the peak period with high daily biogas yields. Meanwhile, the methane (CH4) contents in the Fe(2+) added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 43 publications
3
25
1
Order By: Relevance
“…An analysis of the enzymatic activity would also offer an elegant way to better evaluate the effects of TE addition on the activity of the microbial enzymes, including cellulases that are responsible for the hydrolysis of the cellulose contained in the rice straw [41]. Zhang et al [42] and Tian et al [43] showed a positive effect of Fe and Ni in enhancing the biogas production yields from cow dung and Phragmites straw, respectively, ascribing this also to a stimulation of the cellulase activity. Ni has also been reported to be an essential co-factor for enzymes involved in both the acetoclastic and hydrogenotrophic pathways for methanogenesis [44].…”
Section: Effect Of Fe and Co Addition On Biomethane Production And Vfmentioning
confidence: 99%
“…An analysis of the enzymatic activity would also offer an elegant way to better evaluate the effects of TE addition on the activity of the microbial enzymes, including cellulases that are responsible for the hydrolysis of the cellulose contained in the rice straw [41]. Zhang et al [42] and Tian et al [43] showed a positive effect of Fe and Ni in enhancing the biogas production yields from cow dung and Phragmites straw, respectively, ascribing this also to a stimulation of the cellulase activity. Ni has also been reported to be an essential co-factor for enzymes involved in both the acetoclastic and hydrogenotrophic pathways for methanogenesis [44].…”
Section: Effect Of Fe and Co Addition On Biomethane Production And Vfmentioning
confidence: 99%
“…Iron also improved overall microbial activity, suggested by the increasing CO 2 generation with the increasing Fe concentration. Combined with above results on methane production, it is possible that Fe addition stimulated substrate hydrolysis of lignocellulosic biomass , and the hydrolysate further provided substrates for both CO 2 and methane generation.…”
Section: Resultsmentioning
confidence: 57%
“…The COD were generally lower in Fe-added groups than in the control group [46]. Fe addition induced a stable and excellent COD conversion rate suggesting a more efficient utilization of soluble organic components in the fermenter that consequently improves biogas yields [47].…”
Section: Variation Of Chemical Oxygen Demands (Cod)mentioning
confidence: 91%